An effective method for establishing a regeneration and genetic transformation system for Actinidia arguta - Yao, Wantian; Kong, Lingling; Lei, Diya; Zhao, Bing; Tang, Honglan; Zhou, Xuan; Lin, Yuanxiu; Zhang, Yunting; Wang, Yan; He, Wen; Li, Mengyao; Chen, Qing; et al. (Frontiers in Plant Science, 2023)
The experimental aim of this research was to create an efficient and stable genetic transformation method for hardy kiwi (Actinidia arguta). The different conditions favoring plant regeneration were studied, as well as the main variables driving the genetic transformation of the callus. Aseptic seedling leaves of A. arguta were used as callus-inducing materials. MS medium supplemented with 0.3 mg·L-1 2,4-D and 1.0 mg·L-1 BA was the optimal medium for callus induction of leaves, and medium supplemented with 3 mg·L-1 tZ and 0.5 mg·L-1 IAA was optimal for adventitious shoot regeneration. The best proliferation medium for adventitious buds was MS+ 1.0 mg·L-1 BA + 0.3 mg·L-1 NAA, with a proliferation rate of 3.57. The best rooting medium was 1/2MS + 0.7 mg·L-1 IBA with a 100% rooting rate, root length of 2.81 cm, and average root number of 14.50. For the red flesh hardy kiwi variety ‘Purpurna Saduwa’ (A. arguta var. purpurea), leaves are receptors for Agrobacterium (EHA105)-mediated transformation. GUS-staining was utilized to determine the best parameters for the transformation system. The genetic transformation rate of leaves is as high as 21% under the best conditions of pre-cultivation for four days: OD600 of 0.4–0.6, infection for 20–30 min, the addition of 100 µmol·L-1 AS (acetosyringone) to the culture broth and co-culture medium, and co-cultivation for three days. We used 10 mg·L-1 Hyg (hygromycin B) as the critical concentration for resistance screening, and GUS-staining was done on the resistant callus. The resistant callus stained blue, confirming that the foreign gene had been incorporated into the genome. Our study provides technical parameters for applying genetic resources and molecular breeding of kiwifruit with red flesh.